2009
DOI: 10.1097/coh.0b013e32832f011e
|View full text |Cite
|
Sign up to set email alerts
|

New virologic reagents for neutralizing antibody assays

Abstract: Comprehensive assessment of anti-HIV-1 antibody potency and breadth is essential for evaluating vaccine immunogens, the advancement of vaccine candidates into clinical trials, and ultimately the development of effective vaccine strategies. Env-pseudovirion and recombinant reporter cell line neutralization assays are important tools for rapid and standardized measurement of neutralizing antibody activity. However, recent studies indicate that reporter cell lines fail to detect neutralization activity of certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…8 Furthermore, the molecular strategy was designed to facilitate expression of heterologous env genes in an isogenic (NL4-3-derived) proviral backbone, collectively referred to as Env-IMC-LucR.T2A, or simply LucR.T2A reporter viruses. As previously reported, 3,8 this approach enables sensitive detection of infection, as measured by reporter gene expression, in assays that require replication-competent HIV-1, including those utilizing peripheral blood mononuclear cells (PBMCs) or other primary cells and nonreporter T cell lines.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…8 Furthermore, the molecular strategy was designed to facilitate expression of heterologous env genes in an isogenic (NL4-3-derived) proviral backbone, collectively referred to as Env-IMC-LucR.T2A, or simply LucR.T2A reporter viruses. As previously reported, 3,8 this approach enables sensitive detection of infection, as measured by reporter gene expression, in assays that require replication-competent HIV-1, including those utilizing peripheral blood mononuclear cells (PBMCs) or other primary cells and nonreporter T cell lines.…”
mentioning
confidence: 89%
“…5 and 6), we investigated alternative reporter virus strategies that utilized an IRES bicistronic reporter system. We and others have found the performance of previous EMCV IRES HIV-1 reporter viruses (e.g., NLENG1i) 3,[27][28][29] to be suboptimal with respect to replication, stability of the EGFP reporter gene (personal observations), and supraphysiological overexpression of Nef.…”
Section: Derivation Of Novel Lucrires Reporter Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…KK10-specific TCR expression by the transduced CD8 ϩ T cells was determined by sequential staining with PE-labeled HLAB*2705/KK10 dextramer for 10 min at room temperature and with Pacific Blue-labeled anti-CD8a antibody (BD Biosciences) for 20 min at 4°C followed by washing with PBS and analysis by flow cytometry. In parallel, HLA-B*2705-expressing GXR cells (1 ϫ 10 5 cells/well) were infected in 96-well plates with HIV-LucR (MOI, ϳ0.5), an infectious HIV-1 molecular clone that expresses the HIV-1 JR-CSF Env and a Renilla reniformis luciferase (LucR) reporter gene (67,68). One day later, the HIV-1-infected GXR cells and either mock-transduced or lentivirus-transduced CD8 ϩ T cells were added at an effector-to-target ratio of 1:1 in quadruplicate and cultured for an additional 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…For certain experiments, replication competent reporter viruses encoding SIV Env and Renilla luciferase (LucR) were utilized. pNL-LucR.T2A-SIVagm.sab92018.ps was constructed by modifying the previously described pNL-LucR.T2A-Env.ecto HIV-1 reporter virus approach (29,30) such that SIV env genes of interest could be expressed in an established robust, isogenic reporter virus backbone. It has been previously reported that SIV Env cytoplasmic tail truncations to 22 or 23 amino acids (aa) are selected for by replication of SIVmac in human cells, including PBMCs (31).…”
Section: Study Animals and Specimen Collection Six Female Agms And 4mentioning
confidence: 99%